ISOLASI DAN IDENTIFIKASI Streptococcus sp. PENYEBAB PENYAKIT PADA NILA MERAH (Oreochromis sp.) DARI KABUPATEN SLEMAN DAN KLATEN - , ROSA EIRE REZEKI, Dr.Ir. Murwantoko, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objectives of the research were to isolate, to identify Streptococcus sp. and to determine the causative disease of their pathogenicity on tilapia (Oreochromis sp.). The samples were collected from three different areas in Sleman and Klaten Regency. The bacteria were isolated from the samples then continue by postulate Koch test by intramuscular injection at 0,1 ml/fish and observed for itâs symptoms. The characterization and identification were done from morphology of bacterial colony and cell, physiological and biochemical properties. Pathogenicity test were done by injection at the various concentration as 104,106,108cfu/fish into the tilapia with size range of 5 to 7 cm and determined itâs Lethal Dosage value of 50 (LD50). The 32 isolates have been purified and 25 isolates among them were Streptococcus sp .Twelve isolates confirmed as pathogens which divided into 8 isolates (CK II.1, MK III.2, JT V.1, JT V.2, JT VI, JT VII.2, JT VIII, and JT IX.2.) were identified as S. agalactiae and 4 isolates (CK I.1, MK IV, MK V.2, and JT V.3) were identified as S. iniae. The general symptoms of Streptococcus sp. including the abnormal swimming behavior and exophthalmos. The isolate of S. agalactiae (CK II.1, MK III.2 and JT VI) were virulent with the LD50 4,36.105